2004
DOI: 10.1021/ma049557f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Characterization of Small Band Gap Poly(3,4-ethylenedioxythiophene methine)s

Abstract: Theoretical and experimental characterization of relatively small band gap methine-bridged poly(3,4-ethylenedioxythiophene)(PEDOT) derivatives is reported. AM1 and the modified extended Hückel theory were used to explore the ground-state geometric and electronic structures of poly[(3,4-ethylenedioxythiophene-2,5-diyl) methine] (PEDOT-M). The bond length alteration in PEDOT-M was found to be smaller than that in the reported methine-bridged polythiophene, and this resulted in a significantly lower band gap of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 51 publications
6
32
0
Order By: Relevance
“…The bandgap as well as the molecular energy level of P(BDT-T) is similar with that of H6, the results indicated that different alkoxyl chains on the BDT unit influence the energy bandgap of polymers very little. The electrochemical bandgap of P(BDT-T) and P(BDT-TT) is a little higher than that of the optical bandgap aforementioned, which is a common phenomenon for the conjugated polymers [42,43].…”
Section: Electrochemical Propertiesmentioning
confidence: 92%
“…The bandgap as well as the molecular energy level of P(BDT-T) is similar with that of H6, the results indicated that different alkoxyl chains on the BDT unit influence the energy bandgap of polymers very little. The electrochemical bandgap of P(BDT-T) and P(BDT-TT) is a little higher than that of the optical bandgap aforementioned, which is a common phenomenon for the conjugated polymers [42,43].…”
Section: Electrochemical Propertiesmentioning
confidence: 92%
“…For PEDOT and derivatives thereof, absorption spectroscopy indicates that the difference in the gap is less than 0.1 eV between PE-DOT in solution and PEDOT in film form. 38,40 The computed band gap also depends quite sensitively on the computational approach used. Especially the discontinuity in the exchange-correlation functional is often pointed out as the main source of error.…”
Section: 253435mentioning
confidence: 99%
“…Poly(heteroarylene methine)s, are a kind of conjugated polymers, which are promising materials since they are low band gap polymers which have attractive a great deal of attention due to their intrinsic electronic, optoelectronic, optical and nonlinear properties [15]. Little study has been reported about water-soluble poly(heteroarylene methine)s, although water-soluble conjugated polymers have been extensively investigated for chemical and biological sensing applications.…”
Section: Introductionmentioning
confidence: 99%